Effects of acupuncture treatment on microRNAs expression in ovarian tissues from Tripterygium glycoside-induced diminished ovarian reserve rats - Lu, Ge; Zhu, Yao-yao; Li, Hong-xiao; Yin, Yao-li; Shen, Jie; Shen, Mei-hong (Frontiers in Genetics, 2022)
Acupuncture is widely used to improve ovarian function. Previously, we have demonstrated that acupuncture can improve oxidative stress in rats with tripterygium glycoside tablet suspension (TGs)-induced diminished ovarian reserve (DOR). Herein, we aimed to explore the anti-oxidation mechanism of acupuncture for ameliorating ovarian reserve in DOR rats. We performed microRNA sequencing and bioinformatics analysis to screen differentially expressed miRNAs (DE miRNAs) in ovarian tissues. In total, 1172 miRNAs were identified by miRNA sequencing, of which 28 DE miRNAs were detected (including 14 upregulated and 14 downregulated) in ovarian tissues from the acupuncture group when compared with the DOR model rats. Based on functional enrichment analysis, target genes of DE miRNAs were significantly enriched in GO-biological process (BP) terms associated with biological processes, positive regulation of transcription by RNA polymerase II, signal transduction, regulation of transcription, DNA-templated processes, and oxidation-reduction processes. In the Kyoto Encyclopedia of Genes and Genomes analysis, the main pathways were the MAPK signaling pathway, hepatitis B, proteoglycans in cancer, human cytomegalovirus infection, and the Ras signaling pathway. Finally, reverse transcription-quantitative PCR results confirmed that rno-miR-92b-3p, mdo-miR-26b-5p_R+1_1ss10TC, and bta-miR-7857-3p_R-1 were downregulated in the acupuncture group. The results revealed the impact of acupuncture on miRNA profiling of ovarian tissues from DOR rats, suggesting that rno-miR-92b-3p, mdo-miR-26b-5p_R+1_1ss10TC, and bta-miR-7857-3p_R-1 might provide relevant cues to relieve DOR-mediated oxidative stress.